Correlation between lifestyles of tobacco smoking and alcohol drinking, and expression of p53 and GLUT1 in synchronous oral squamous cell carcinoma with colorectal cancer. Issue 6 (November 2022) - Asahara, Fumitaka; Yamazaki, Masae; Kokubun, Katsutoshi; Matsuzaka, Kenichi; Kishikawa, Hiroshi; Matsui, Junichi; Nomura, Takeshi
Abstract: Objective: The concept of field cancerization has been applied to synchronous cancers associated with specific lifestyles. Common risk factors between oral squamous cell carcinoma and colorectal cancer are suspected. The aim of this study is to identify the correlation between clinical factors, such as smoking and drinking, in patients with synchronous oral squamous cell carcinoma and colorectal cancer. Furthermore, the impact of these lifestyle factors according to the expression of p53 and GLUT1 was considered. Methods: 673 oral carcinoma patients who received definitive therapy at our hospital between 2009 and 2020 were targeted. 653 individuals were assigned to screening for secondary primary tumors by 18FDG-PET/CT and/or colonoscopy. Lifestyle factors were epidemiologically investigated and the clinicopathologic implications of the expression of lifestyle biomarkers p53 and GLUT1 were examined. Results: Among 653 patients, 11 (1.7%) were identified as synchronous colorectal cancer. Although the study data did not show any statistically significant differences, these patients had an increased tendency of smoking and drinking. Furthermore, greater p53 and GLUT1 expression was observed in the patients with smoking and drinking habits. Conclusions: Colorectal cancer should be recognized as a second primary tumour of oral carcinoma. Screening with 18 FDG-PET/CT and colonoscopy, particularly for oral carcinoma patients with smoking and drinking habits, should be routine practice to detect colorectal cancer. Furthermore, the degree of p53 and GLUT1 expression was higher in patients identified as smokers and drinkers. From these results, characterization of the oral cavity and colorectum as genetically altered fields is suggested.